Reactive PLIF method for characterisation of micromixing in continuous high-throughput chemical reactors - Ribeiro, João Peres (2022)
This work aimed to test and optimise reactive Planar Laser-Induced Fluorescence (PLIF) methods for the visualisation of the micromixing regions in chemical reactors using standard PLIF and Particle Image Velocimetry (PIV) equipment with the laser source 512 nm. Two methods were tested: (i) an acid–base reaction with fluorescein as the reaction-sensitive tracer and (ii) Fenton’s reaction, with Rhodamine B as the reaction tracer. Both test-reactions were studied in stopped-flow equipment to define suitable operational conditions, namely the chemical composition of the inflow streams, the concentration of reagents and fluorophore, and suitable excitation light wavelength. The visualisation of the micromixing regions was tested in a continuous flow reactor with a T-jet geometry. A laser light sheet emitted from an Nd:YAG laser illuminated the axial section of the demonstration reactor. The mixing dynamics and the reaction course were visualised with the acid–base reactive PLIF images. Fenton’s reactive PLIF method showed the overall distribution of mixing and reaction regions. The main contribution of this work is benchmarking two methods with costs that enable the visualisation of micromixing regions in continuous high-throughput reactors.